Effectiveness of Using Memorisation Technique to Expand Students' English Vocabulary - Hafsari, Ria; Syarifuddin, Syarifuddin; Sartika, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The effectiveness of using memorisation techniques to expand students‘ English vocabulary aims to examine how memorisation techniques can be effectively applied to expand students’ English vocabulary, as well as the positive impacts that can result from the application of these techniques in the context of foreign language learning. This research uses a qualitative approach with descriptive methods to explore the effectiveness of memorisation techniques in expanding the English vocabulary of primary school students. A structured, interactive and fun memorisation method can help students to expand their English vocabulary effectively. With a combination of repetition techniques, games, visualisation, and application of vocabulary in sentences and dialogues. The results obtained in this tutoring activity are students get basic knowledge of vocabulary related to frequently used verbs, students can practice directly how to pronounce and pronounce vocabulary correctly, and students get the experience of learning English in a fun way. The results emphasise how important it is to master vocabulary when learning English, especially for students in primary school. Important words that must be understood for better communication skills in English, both when speaking and writing. It is hoped that this research can provide insights for educators and education managers in designing more innovative and efficient learning methods to improve students' language skills.